A Cu-Fe-ZIF-8 / GCN composite material and its preparation method and application
By compositeing Fe ions and GCN with ZIF-8 and doping Cu ions, Cu-Fe-ZIF-8/GCN composite material is prepared, which solves the problem of low efficiency in removing TC in wastewater in the prior art, and achieves efficient TC adsorption and reusability.
Patent Information
- Application Number
- CN202310077848.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-01-31
AI Technical Summary
The prior art removes antibiotic residues in wastewater, especially tetracycline hydrochloride (TC), and the aging is not significant enough and it is difficult to achieve efficient biodegradation.
Fe ions and graphite phase carbon nitride (GCN) were compounded with ZIF-8 by one pot cooking method to form a Fe-ZIF-8/GCN composite material, and Cu ions were doped into Fe-ZIF-8/GCN by ion exchange method to prepare Cu-Fe-ZIF-8/GCN composite material.
The Cu-Fe-ZIF-8/GCN composite material exhibits extremely high adsorption capacity in adsorption and removal of TC in aqueous solution, 4.9 times higher than the original ZIF-8, and still maintains an adsorption capacity of more than 85% after four cycles. The preparation process is simple and suitable for large-scale production.
Smart Images

Figure CN116173887B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, in particular to a Cu-Fe-ZIF-8 / GCN composite material and a preparation method and application thereof. Background Art
[0002] Antibiotics, as a drug ingredient, are widely used in medicine and agriculture because they can effectively inhibit and kill bacteria. Tetracycline hydrochloride (TC), as one of the common antibiotics, is not easily degraded or removed in traditional sewage treatment plants due to its strong hydrophilicity and structural stability. It is also extremely difficult to be biodegraded in the natural environment. Over time, it will continue to accumulate in various water environments. It has been reported that antibiotic residues have been detected in various water environments, including sediments, surface water, and even groundwater. In order to prevent its long-term adverse effects, it is very necessary to develop advanced technologies to remove organic pollutants from wastewater. Metal-organic frameworks (MOFs) are a kind of porous crystalline materials self-assembled by metal ions or metal clusters and organic ligands. Zinc-based zeolitic imidazole framework (ZIF-8) can be synthesized with Zn ions and 2-methylimidazole to form a three-dimensional zeolite structure. Since ZIF-8 can be synthesized at room temperature and has a stable structure, it has great potential in wastewater treatment. However, when ZIF-8 is used alone, the removal efficiency is not significant enough and needs to be modified. Graphitic carbon nitride (g-C3N4, abbreviated as GCN) is a new type of carbon nanomaterial and also a chemically stable metal-free semiconductor. The embedded functional groups (-NH2 / -NH- / =N-) of GCN have a π-conjugated planar layer structure, and these chemical properties can provide rich interaction sites for different types of pollutants. Doping modification with transition metals such as Fe and Cu is also an effective way to improve the performance of materials. Combining GCN and transition metals with ZIF-8 will help improve the performance of materials. For this purpose, a Cu-Fe-ZIF-8 / GCN composite material and its preparation method and application are provided. Summary of the invention
[0003] The purpose of the present invention is to provide a Cu-Fe-ZIF-8 / GCN composite material and a preparation method and application thereof in view of the defects of the prior art, so as to solve the problems raised by the above-mentioned background technology.
[0004] To achieve the above object, the present invention provides the following technical scheme: a Cu-Fe-ZIF-8 / GCN composite material, wherein Fe ions and GCN are compounded with ZIF-8 by a one-pot method and then compounded with Cu ions by an ion exchange method to synthesize Cu-Fe-ZIF-8 / GCN; the specific surface area of the Cu-Fe-ZIF-8 / GCN composite material is 519 m 2 / g, and the total pore volume is 0.44cm 3 / g, and the average pore size is 3.4nm.
[0005] A method for preparing a Cu-Fe-ZIF-8 / GCN composite material comprises the following steps:
[0006] S1: Preparation of GCN: Melamine was placed in a crucible, then transferred to a muffle furnace for heating, and kept at 550°C for a certain period of time, and finally cooled and taken out for grinding to obtain GCN;
[0007] S2: Preparation of Fe-ZIF-8 / GCN: zinc acetate dihydrate, ferric nitrate nonahydrate and GCN were added to deionized water and ultrasonically treated for a period of time; then, 2-methylimidazole was added to another deionized water, stirred until clear, poured into the previously ultrasonically treated mixed solution, stirred for a period of time, and then allowed to stand for a period of time, centrifuged and dried to obtain Fe-ZIF-8 / GCN;
[0008] S3: Preparation of Cu-Fe-ZIF-8 / GCN: A certain amount of Fe-ZIF-8 / GCN was added to an ethanol solution containing copper nitrate trihydrate and stirred for a period of time, and then centrifuged and dried to obtain Cu-Fe-ZIF-8 / GCN.
[0009] As a preferred technical solution of the present invention, the heating rate of melamine in S1 is 2.5°C / min; and the heat preservation time is 4h.
[0010] As a preferred technical solution of the present invention, the molar ratio of 2-methylimidazole to zinc acetate dihydrate and ferric nitrate nonahydrate in S2 is 160:19:1; the mass ratio of zinc acetate dihydrate to GCN is 10-11:1.
[0011] As a preferred technical solution of the present invention, the mass ratio of Fe-ZIF-8 / GCN to copper nitrate trihydrate in S3 is 0.5:2.4.
[0012] As a preferred technical solution of the present invention, the ultrasonic treatment time in S2 is 1 hour; the stirring time in the mixed solution is 2 hours; and the standing time of the mixed solution is 24 hours.
[0013] As a preferred technical solution of the present invention, the stirring time of Fe-ZIF-8 / GCN in S3 in copper nitrate trihydrate solution is 1 hour; the centrifugal speed is 10000r / min; the drying temperature is 70°C, and the drying time is 8 hours.
[0014] As a preferred technical solution of the present invention, the centrifugal speed in S2 is 10000r / min; the drying temperature is 70°C, and the drying time is 8h;
[0015] An application of a Cu-Fe-ZIF-8 / GCN composite material, and an application of the Cu-Fe-ZIF-8 / GCN composite material in adsorbing and removing organic pollutants TC in aqueous solution.
[0016] The beneficial effects of the present invention are:
[0017] The synthesis principle of Cu-Fe-ZIF-8 / GCN of the present invention is as follows: Fe ions and GCN are compounded with ZIF-8 to generate Fe-ZIF-8 / GCN by a one-pot method, and Cu is then doped into Fe-ZIF-8 / GCN by an ion exchange method to obtain Cu-Fe-ZIF-8 / GCN.
[0018] The adsorption mechanism of TC by Cu-Fe-ZIF-8 / GCN of the present invention: The main adsorption mechanism of TC by Cu-Fe-ZIF-8 / GCN is complexation, electrostatic effect, hydrogen bond interaction and π-π interaction.
[0019] (1) Cu-Fe-ZIF-8 / GCN has an extremely high adsorption capacity, which is 4.9 times that of the original ZIF-8;
[0020] (2) Cu-Fe-ZIF-8 / GCN has high reusability and can maintain more than 85% of the initial adsorption capacity after four cycles;
[0021] (3) The preparation of Cu-Fe-ZIF-8 / GCN is simple, the composite process is carried out at room temperature, the solvent is pollution-free, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a graph showing the surface morphology of Cu-Fe-ZIF-8 / GCN prepared in Example 1, GCN prepared in Comparative Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3, and Fe-ZIF-8 / GCN prepared in Comparative Example 4, using a scanning electron microscope;
[0023] Figure 2 a is a graph showing the XRD characterization results of Cu-Fe-ZIF-8 / GCN prepared in Example 1, GCN prepared in Comparative Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4 using an X-ray diffractometer in the present invention;
[0024] Figure 2b is a spectrum analysis diagram of Cu-Fe-ZIF-8 / GCN prepared in Example 1, GCN prepared in Comparative Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4 by Fourier transform infrared spectroscopy of the present invention;
[0025] Figure 3 N2 adsorption-desorption isotherms of Cu-Fe-ZIF-8 / GCN prepared in Example 1 of the present invention, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3, and Fe-ZIF-8 / GCN prepared in Comparative Example 4;
[0026] Figure 4 It is an adsorption equilibrium curve diagram of TC for Cu-Fe-ZIF-8 / GCN prepared in Example 1 of the present invention, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4;
[0027] Figure 5 TC adsorption diagram of Cu-Fe-ZIF-8 / GCN under different adsorption cycles of the present invention;
[0028] Figure 6 Some key pore parameter diagrams of ZIF-8, ZIF-8 / GCN, Fe-ZIF-8 / GCN and Cu-Fe-ZIF-8 / GCN are summarized for the present invention. DETAILED DESCRIPTION
[0029] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0030] The present invention provides a technical solution: a Cu-Fe-ZIF-8 / GCN composite material, wherein Fe ions and GCN are compounded with ZIF-8 by a one-pot method and then compounded with Cu ions by an ion exchange method to synthesize Cu-Fe-ZIF-8 / GCN; the specific surface area of the Cu-Fe-ZIF-8 / GCN composite material is 519m 2 / g, and the total pore volume is 0.44cm 3 / g, and the average pore size is 3.39nm.
[0031] A method for preparing a Cu-Fe-ZIF-8 / GCN composite material comprises the following steps:
[0032] S1: Preparation of GCN: Melamine was placed in a crucible, then transferred to a muffle furnace for heating, and kept at 550°C for a certain period of time, and finally cooled and ground to obtain GCN; the heating rate of melamine was 2.5°C / min; the holding time was 4h;
[0033] S2: Preparation of Fe-ZIF-8 / GCN: zinc acetate dihydrate, ferric nitrate nonahydrate and GCN were added to deionized water and ultrasonically treated for a period of time; then, 2-methylimidazole was added to another deionized water, stirred until clear, poured into the previously ultrasonically treated mixed solution, stirred for a period of time, and then allowed to stand for a period of time, centrifuged and dried to obtain Fe-ZIF-8 / GCN;
[0034] The molar ratio of 2-methylimidazole to zinc acetate dihydrate and ferric nitrate nonahydrate is 160:19:1; the mass ratio of zinc acetate dihydrate to GCN is 10-11:1; the ultrasonic treatment time is 1 hour; the stirring time in the mixed solution is 2 hours; the standing time of the mixed solution is 24 hours; the centrifugal speed is 10000 r / min; the drying temperature is 70°C and the drying time is 8 hours;
[0035] S3: Preparation of Cu-Fe-ZIF-8 / GCN: a certain amount of Fe-ZIF-8 / GCN was added to an ethanol solution containing copper nitrate trihydrate and stirred for a period of time, and then centrifuged and dried to obtain Cu-Fe-ZIF-8 / GCN;
[0036] The mass ratio of Fe-ZIF-8 / GCN to copper nitrate trihydrate is 1:4.8; the stirring time of Fe-ZIF-8 / GCN in copper nitrate trihydrate solution is 1 hour; the centrifugal speed is 10000r / min; the drying temperature is 70°C, and the drying time is 8 hours.
[0037] An application of a Cu-Fe-ZIF-8 / GCN composite material, and an application of the Cu-Fe-ZIF-8 / GCN composite material in adsorbing and removing organic pollutants TC in aqueous solution.
[0038] Embodiment 1:
[0039] The preparation of Cu-Fe-ZIF-8 / GCN composite material includes the following steps:
[0040] 1.04 g of zinc acetate dihydrate, 0.1 g of ferric nitrate nonahydrate and 0.1 g of GCN were added to 25 mL of deionized water and ultrasonically treated for 1 hour; subsequently, 3.28 g of 2-methylimidazole was added to 25 mL of deionized water, stirred until clear, poured into the ultrasonically treated mixed solution and stirred for 2 hours, then allowed to stand for 24 hours, then centrifuged at 10000 r / min for 10 min, washed three times with ethanol by centrifugation, collected the material and dried at 70°C for 8 h to obtain Fe-ZIF-8 / GCN; 0.5 g of Fe-ZIF-8 / GCN was taken out and poured into 40 mL of ethanol solution containing 0.24 g of copper nitrate trihydrate, stirred for 1 hour, then centrifuged at 10000 r / min for 10 min, washed three times with ethanol by centrifugation, and the dried material was collected to obtain Cu-Fe-ZIF-8 / GCN.
[0041] Comparative Example 1:
[0042] Preparation of GCN: Melamine was placed in a crucible and then transferred to a muffle furnace for heating (2.5°C
[0043] / min), and kept at 550℃ for 4h. Finally, it was cooled down, taken out and ground to obtain GCN.
[0044] Comparative Example 2:
[0045] Preparation of ZIF-8: Dissolve 1.1 g of zinc acetate dihydrate in 25 mL of deionized water, and dissolve 3.28 g of 2-methylimidazole in another 25 mL of deionized water. Stir the two solutions until clear, then pour the 2-methylimidazole solution into the zinc acetate dihydrate solution, stir for 2 hours, let it stand for 24 hours, then take out the solution, centrifuge it at 10,000 r / min for 10 minutes, wash it three times with ethanol by centrifugation, collect the material and dry it at 70°C for 8 hours to obtain ZIF-8.
[0046] Comparative Example 3:
[0047] Preparation of ZIF-8 / GCN: 1.1 g of zinc acetate dihydrate and 0.1 g of GCN were added to 25 mL of deionized water and ultrasonically treated for 1 hour; then, 3.28 g of 2-methylimidazole was added to 25 mL of deionized water, stirred until clear, poured into the ultrasonically treated mixed solution and stirred for 2 hours, then allowed to stand for 24 hours, and then centrifuged at 10000 r / min for 10 minutes. After centrifugation and washing three times with ethanol, the material was collected and dried at 70°C for 8 hours to obtain ZIF-8 / GCN.
[0048] Comparative Example 4:
[0049] Preparation of Fe-ZIF-8 / GCN: 1.04 g of zinc acetate dihydrate, 0.1 g of ferric nitrate nonahydrate and 0.1 g of GCN were added to 25 mL of deionized water and ultrasonically treated for 1 hour. Subsequently, 3.28 g of 2-methylimidazole was added to 25 mL of deionized water, stirred until clear, poured into the ultrasonically treated mixed solution and stirred for 2 hours, then allowed to stand for 24 hours, then centrifuged at 10000 r / min for 10 minutes, washed three times by centrifugation with ethanol, and the collected material was dried at 70°C for 8 hours to obtain Fe-ZIF-8 / GCN.
[0050] Material characterization analysis:
[0051] (I) SEM analysis:
[0052] The surface morphologies of Cu-Fe-ZIF-8 / GCN prepared in Example 1, GCN prepared in Comparative Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4 were characterized by scanning electron microscopy.
[0053] The characterization results are as follows Figure 1 As shown in Figure 2, the morphology and surface of ZIF-8, GCN, ZIF-8 / GCN, Fe-ZIF-8 / GCN and Cu-Fe-ZIF-8 / GCN were analyzed by scanning electron microscopy (SEM). Figure 1 As can be seen from a, ZIF-8 crystals have a rhombic dodecahedral morphology, a smooth surface, and an average diameter of about 1 μm. Figure 1 b It can be seen that GCN presents a typical layered and tightly stacked morphology. Figure 1 c is the composite product of ZIF-8 and GCN, in which the diameter of some grains increases and wrinkles appear on the surface. Figure 1 In Figure d, Fe-ZIF-8 / GCN appears as a block agglomerate with a smooth surface. This is because the addition of Fe ions promotes the agglomeration of GCN and replaces part of the Zn ions during the synthesis process, resulting in insufficient grain growth. Figure 1 As shown in Figure e, its surface appears to be relatively rough compared with that of Fe-ZIF-8 / GCN, and a large number of fine grains are formed, which may be because Cu partially replaces part of Fe and Zn. Figure 1 The corresponding energy dispersive X-ray spectroscopy (EDS) element mapping spectrum is as follows Figure 1 As shown in Fig. fj, the element mapping of Cu, Fe, Zn, and N is consistent with the element mapping of C, which indicates that the Cu and Fe elements are evenly distributed on the skeleton and successfully doped into the ZIF-8 crystal.
[0054] (ii) XRD analysis:
[0055] The Cu-Fe-ZIF-8 / GCN prepared in Example 1, the GCN prepared in Comparative Example 1, the ZIF-8 prepared in Comparative Example 2, the ZIF-8 / GCN prepared in Comparative Example 3 and the Fe-ZIF-8 / GCN prepared in Comparative Example 4 were characterized by XRD using an X-ray diffractometer.
[0056] The characterization results are as follows Figure 2 As shown in a, the synthesized ZIF-8 and GCN match well with the spectra obtained in previous literature, indicating that ZIF-8 and GCN were successfully synthesized. GCN has two typical peaks at 2θ values of 13° and 27.4°, representing the (100) crystal plane and (002) crystal plane of the material, respectively. ZIF-8 has peaks at 7.3°, 10.4°, 12.7°, 14.7°, 16.4°, 18°, 22.1°, 24.5°, 26.6° and 29.7°, corresponding to the (011), (002), (112), (022), (013), (222), (114), (233), (134) and (044) crystal planes, respectively. The main characteristic peaks of GCN and ZIF-8 exist in ZIF-8 / GCN, but due to the low content of GCN, the intensity of its corresponding characteristic peak is weak, but the intensity of the corresponding characteristic peak of ZIF-8 has increased, because the crystallinity of ZIF-8 increases due to the influence of GCN during the synthesis process. Although Fe-ZIF-8 / GCN still retains the characteristic peaks corresponding to ZIF-8, the intensity of the diffraction peak is greatly reduced, which means that the crystallinity of the grains is weakened.
[0057] The XRD spectrum of Cu-Fe-ZIF-8 / GCN shows that the diffraction peak belonging to ZIF-8 increases again. This is because the doping of Cu element replaces part of the Fe ions and Zn ions, which improves the crystallinity of the material. The above results show that GCN, Fe, and Cu are fully compounded in ZIF-8, which is conducive to increasing a large number of adsorption active sites and binding sites.
[0058] (III) FT-IR analysis:
[0059] Fourier transform infrared spectroscopy was used to perform spectral analysis on Cu-Fe-ZIF-8 / GCN prepared in Example 1, GCN prepared in Comparative Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4.
[0060] Figure 2 b shows that for ZIF-8, 3400 cm -1 The broad absorption band near 2930 cm-1 is related to the stretching vibration of the -OH group. -1 The peak at 1580 cm is the stretching vibration peak of the CH bond in the imidazole ring. -1The stretching vibration peak of C=N is 1150cm -1 and 993cm -1 The peaks at 808cm are the stretching vibration absorption peaks of CN in the imidazole ring, which is consistent with the characteristics of the literature. These peaks still exist in the subsequent composite materials, indicating that the structure of the ZIF-8 functional group is stable. In the FT-IR spectrum of GCN, 808cm -1 The peak at 1640cm is caused by the bending vibration of the triazine ring. -1 and 1240cm -1 The corresponding CN heterocycles were also reflected in the subsequent composite materials, which means the successful composite of GCN. The doping of Cu and Fe did not make the characteristic peaks of ZIF-8 / GCN disappear, which means that the doping of the two did not lead to the change of the functional groups of ZIF-8.
[0061] (IV) N2 adsorption-desorption isotherm analysis:
[0062] The specific surface areas of Cu-Fe-ZIF-8 / GCN prepared in Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3 and Fe-ZIF-8 / GCN prepared in Comparative Example 4 were determined by N2 adsorption-desorption isothermal analysis.
[0063] Figure 3 N2 adsorption-desorption isotherms of Cu-Fe-ZIF-8 / GCN prepared in Example 1, ZIF-8 prepared in Comparative Example 2, ZIF-8 / GCN prepared in Comparative Example 3, and Fe-ZIF-8 / GCN prepared in Comparative Example 4. ZIF-8, ZIF-8 / GCN, Fe-ZIF-8 / GCN, and Cu-Fe-ZIF-8 / GCN all show typical IV type isotherms with obvious hysteresis loops, which are conducive to the generation of pores in the material. ZIF-8, ZIF-8 / GCN, Fe-ZIF-8 / GCN, and Cu-Fe-ZIF-8 / GCN all show typical IV type isotherms with obvious hysteresis loops, which benefit from the generation of pores in the material. It is worth noting that the hysteresis loop of Cu-Fe-ZIF-8 / GCN is the most significant. Figure 6Some key pore parameters of ZIF-8, ZIF-8 / GCN, Fe-ZIF-8 / GCN and Cu-Fe-ZIF-8 / GCN were summarized. The doping of GCN did not improve the physical parameters of ZIF-8 such as specific surface area and pore size. The doping of Fe ions gave full play to the advantages of high specific surface area of ZIF-8. Even if the specific surface area of the composite material after doping was reduced, it could still be maintained at a high level, and the problem of small pore size of the material hindering adsorption was improved. The introduction of Cu ions increased both the specific surface area and the average pore size of Fe-ZIF-8 / GCN, and the total pore volume was also significantly increased. Among the several composite materials displayed, the pore size of Cu-Fe-ZIF-8 / GCN was the most significantly improved compared with the original ZIF-8. The specific surface area of ZIF-8 increased from 975m 2 g -1 Down to 519m 2 g -1 At the same time, its pore size was increased from 2.38nm to 3.39nm.
[0064] (V) Reusability:
[0065] In order to investigate the cyclic performance of the material under the condition of the highest adsorption effect, the pH value was set to 6, the adsorbent was selected as Cu-Fe-ZIF-8 / GCN prepared in Example 1, the TC solution volume was 100 mL, and the adsorbent concentration was set to 100 mg L -1 , TC concentration was set to 100 mg L -1 The Cu-Fe-ZIF-8 / GCN adsorbed with TC was washed with 0.01 mol / L NaOH solution and deionized water, and then the material was dried to reactivate the Cu-Fe-ZIF-8 / GCN. The TC adsorption amount of Cu-Fe-ZIF-8 / GCN under different adsorption cycles is shown in Figure 2. Figure 5 It can be observed that after 4 adsorption-desorption cycles, the adsorption capacity of Cu-Fe-ZIF-8 / GCN for TC can still reach 866 mg·g -1 , which is 87.2% of the initial use, which means that this material has good reusability, recycling performance, stability and easy recycling, and has good industrial application value.
[0066] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
Claims
1. A method for preparing a Cu-Fe-ZIF-8 / GCN composite material, characterized in that: The Fe ions and graphite carbon nitride GCN were compounded with ZIF-8 by a one-pot method and then compounded with Cu ions by an ion exchange method to synthesize Cu-Fe-ZIF-8 / GCN; the specific surface area of the Cu-Fe-ZIF-8 / GCN composite material was 519 m 2 / g, and the total pore volume is 0.44cm 3 / g, average pore size is 3.39nm; The specific preparation method of the Cu-Fe-ZIF-8 / GCN composite material comprises the following steps: S1: Preparation of graphite carbon nitride GCN: melamine is placed in a crucible, then transferred to a muffle furnace for heating, and kept at 550°C for a certain period of time, and finally cooled and taken out and ground to obtain graphite carbon nitride GCN; S2: Preparation of Fe-ZIF-8 / GCN: zinc acetate dihydrate, ferric nitrate nonahydrate and graphite carbon nitride GCN were added to deionized water and ultrasonically treated for a period of time; then, 2-methylimidazole was added to another deionized water, stirred until clear, poured into the previously ultrasonically treated mixed solution, stirred for a period of time, and then allowed to stand for a period of time, centrifuged and dried to obtain Fe-ZIF-8 / GCN; The molar ratio of 2-methylimidazole to zinc acetate dihydrate and ferric nitrate nonahydrate is 160:19:1; the mass ratio of zinc acetate dihydrate to graphite carbon nitride GCN is 10-11:1; S3: Preparation of Cu-Fe-ZIF-8 / GCN: a certain amount of Fe-ZIF-8 / GCN was added to an ethanol solution containing copper nitrate trihydrate and stirred for a period of time, and then centrifuged and dried to obtain Cu-Fe-ZIF-8 / GCN; The mass ratio of Fe-ZIF-8 / GCN to copper nitrate trihydrate is 5:2.
4.
2. The method for preparing a Cu-Fe-ZIF-8 / GCN composite material according to claim 1, characterized in that: The heating rate of melamine in S1 is 2.5°C / min; the holding time is 4h.
3. The method for preparing a Cu-Fe-ZIF-8 / GCN composite material according to claim 1, characterized in that: The ultrasonic treatment time in S2 is 1 h; the stirring time in the mixed solution is 2 h; and the standing time of the mixed solution is 24 h.
4. The method for preparing a Cu-Fe-ZIF-8 / GCN composite material according to claim 1, characterized in that: The stirring time of Fe-ZIF-8 / GCN in the copper nitrate trihydrate solution in S3 is 1 hour; the centrifugal speed is 10000 r / min; the drying temperature is 70° C., and the drying time is 8 hours.
5. The method for preparing a Cu-Fe-ZIF-8 / GCN composite material according to claim 1, characterized in that: The centrifugal speed in S2 is 10000 r / min; the drying temperature is 70° C. and the drying time is 8 h.
6. An application of the Cu-Fe-ZIF-8 / GCN composite material prepared by the method of claim 1, characterized in that: Application of Cu-Fe-ZIF-8 / GCN composite materials in the adsorption and removal of organic pollutants TC from aqueous solutions.
Citation Information
Patent Citations
Preparation method and application of Cu-ZIF-8 composite nano material
CN111167412A